„Powinna być nieufnością”. Nowofalowy spór o poezję - Pawelec, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2020)
‘Distrust Should Be Its Mission’. The New Wave Polemic Over Poetry The study undertakes the most important programme presentations from the period of the so-called ferment and tension (1967–1976) of pokolenie 68 (Nowa Fala) [Generation 68 (New Wave)] in Polish Poetry with poets such as Stanisław Barańczak, Adam Zagajewski, Julian Kornhauser and Krzysztof Karasek. The introduction outlines the circumstances tied to the beginnings of this generation’s awareness and subsequent crystallisation as well as the programme theses and polemics within Generation, as well as polemics with literary predecessors (Orientacja Hybrydy, pokolenia 56) [The Hybrid, Generation 56]. Source texts were chosen by dividing into 5 groups the collection of early manifestoes, important drafts of programmes and polemics, proven diagnoses concerning the Generation’s situation and discussion on the so-called thesis on the world not represented – including the intra-Generational polemic over the value of Zbigniew Herbert’s poetry. Finally, completing the study, a discussion on the period of Generation 68’s development of polemic over the actualization of Tomas Mann’s Magic Mountain and it’s reception.
‘Distrust Should Be Its Mission’. The New Wave Polemic Over Poetry